Assimilation of GRACE, satellite Altimetry and Hydrological data for determining mass variations in the Siberian permafrost region - Shabanloui, Akbar; Müller, Jürgen (2014)
The permafrost in Siberia (Russia) plays an important role for the global water cycle and climate change in the Earth system. In this study, data from satellite altimetry missions, hydrological models and GRACE are assimilated to retrieve a more realistic pattern of surface mass variations in Siberia. GRACE provides the integral mass variations with different spatial-temporal resolution depending on the applied filters and reduction models. We used the new release L2 products from GFZ (RL05a) and tested various filters. Geometrically, surface mass variations are determined based on satellite (radar/laser) altimetry tracking data (e.g. Jason-2, ICESat), where especially lake level variations are extracted. In addition, hydrological surface mass variations are obtained from hydrological water cycle models based on observations of precipitation, evapotranspiration and run-off data. We tried to quantify the individual signal contributions in Siberia and to consistently combine the various data to get a better estimate on how big the real permafrost change might be.